Three-dimensional ultrastructural imaging reveals the nanoscale architecture of mammalian cells. (2018) - Yao, Shengkun; Fan, Jiadong; Chen, Zhiyun; Zong, Yunbing; Zhang, Jianhua; Sun, Zhibin
No abstract available